Memoir of My Youth in Cuba : A Soldier in the Spanish Army during the Separatist War, 1895-1898 - Conangla i Fontanilles, Josep, 1875-1965 (Book collections on Project MUSE., 2017)
Memoir of My Youth in Cuba: A Soldier in the Spanish Army during the Separatist War, 1895--1898 is a translation of the memoir Memorias de mi juventud en Cuba: Un soldado del ejercito español en la guerra separatista (1895--1898) by Josep Conangla. The English edition is based on the Spanish version edited by Joaquín Roy, who found the memoir and was given access to the Conangla family archives. Conangla's memoir, now available in English, is an important addition to the accounts of Spanish and Cuban soldiers who served in Cuba's second War of Independence. Spaniard Josep Conangla was conscripted at the age of twenty and sent to Cuba. In the course of his time there, he reaffirmed his pacifism and support of Cuban independence. The young man was a believer who unfailingly connected his view of events to the Christian humanitarianism on which he prided himself. Conangla's advanced education and the influence of well-placed friends facilitated his assignment to safe bureaucratic positions during the war, ensuring that he would not see combat. From his privileged position, he was a keen observer of his surroundings. He described some of the decisions he made, which at times put him at odds with the military bureaucracy he served, along with what he saw as the consequences of General Valeriano Weyler's decree mandating the reconcentración, an early version of concentration camps. What Conangla saw fueled his revulsion at the collusion of the Spanish state and its state-sponsored religion in that policy. "Red Mass," published six years after the War of Independence and included in his memoir, is a vivid expression in verse of his abhorrence. Conangla's recollections of the contacts between Spaniards and Cubans in the areas to which he was assigned reveal his ability to forge friendships even with Creole opponents of the insurrection. As an aspiring poet and writer, Conangla included material on fellow writers, Cuban and Spanish, who managed to meet and exchange ideas despite their circumstances. His accounts of the Spanish defeat, the scene in Havana around the end of the war, along with.